2016
DOI: 10.1038/srep30349
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide emission related to ammonia-oxidizing bacteria and mitigation options from N fertilization in a tropical soil

Abstract: Nitrous oxide (N2O) from nitrogen fertilizers applied to sugarcane has high environmental impact on ethanol production. This study aimed to determine the main microbial processes responsible for the N2O emissions from soil fertilized with different N sources, to identify options to mitigate N2O emissions, and to determine the impacts of the N sources on the soil microbiome. In a field experiment, nitrogen was applied as calcium nitrate, urea, urea with dicyandiamide or 3,4 dimethylpyrazone phosphate nitrificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
92
3
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(110 citation statements)
references
References 45 publications
10
92
3
5
Order By: Relevance
“…From our previous work, we found that bacterial amoA (AOB) but not archaeal amoA (AOA) nor denitrification gene copy numbers (nirK, nirS) were correlated with nitrous oxide emissions from tropical soil growing sugarcane (Soares et al, 2016). Here, we found evidence that the AOB responsible for the N 2 O emissions was most phylogenetically similar to the Nitrosospira spp.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…From our previous work, we found that bacterial amoA (AOB) but not archaeal amoA (AOA) nor denitrification gene copy numbers (nirK, nirS) were correlated with nitrous oxide emissions from tropical soil growing sugarcane (Soares et al, 2016). Here, we found evidence that the AOB responsible for the N 2 O emissions was most phylogenetically similar to the Nitrosospira spp.…”
Section: Discussionmentioning
confidence: 55%
“…Further, the nitrite oxidizer bacteria Nitrobacter and Nitrospira have optimal growth under higher and lower nitrite supplies, respectively, which is linked to their ecological niches (Attard et al, 2010;Nowka et al, 2015). Nitrification is doubly implicated in N 2 O production, either directly or indirectly by producing NO 3 − as the basis for denitrification, and has been shown to be the main process involved in N 2 O emissions in some Brazilian sugarcane soils (Liu et al, 2016;Soares et al, 2016;Wu et al, 2017aWu et al, , 2017bLourenço et al, 2018aLourenço et al, , 2018b. The addition of nitrification inhibitors with nitrogen fertilizers is currently being explored as a sustainable management practice in Brazilian sugarcane Soares et al, 2015Soares et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations